A prediction-correction scheme for forcing alveolar gases along certain time courses. - Robbins, P; Swanson, G; Howson, MG (1982)
A computerized prediction-correction scheme has been devised for the control of alveolar gases. First, a model is run off-line to predict the inspiratory gas tensions at each second that should yield the desired alveolar patterns. Second, during the experiment, there is feedback correction based on the deviation of the actual alveolar values from the desired alveolar values. The actual alveolar values are found by a second computer and passed to the controlling computer using interrupts. The controlling computer has four digital-toi-analog outputs for controlling CO2, O2, N2, and air flows so as to achieve the commanded inspiratory PCO2 and PO2 (CO2 and O2 partial pressures, respectively). The scheme is illustrated for the generation of sinusoidal alveolar PCO2 with alveolar PO2 held constant and for steps of alveolar PCO2 at constant alveolar PO2.